Geological-geotechnical study of the area for the sanitary landfill of the city of Suyo, Ayabaca Province, Piura Department - Allende Ccahuana, Teófilo (2012)
The Suyo Municipality is impelling projects to solve the environmental problem for the inadequate handling of the solid residuals, one of those which is the project of sanitary filler for the city. In this sense, the present study is a basic investigation to develop a project of sanitary filler in an area of 0.75 Has., located in the km 1000 + 132 in the road Sullana-Las Lomas-Suyo, and seated in the alluvial cone of the Qda. Leones, which is part of the flank of the Andes Mountain. The relief has been profiled in sedimentary volcanic rock of the Volcanic Lancones, it is covered for systems alluvial depositacional. The deposits conform a soil of two horizons, a superficial level of clay (CL), and another inferior argillaceous sand (SC) that varies in horizontal sense to argillaceous silt, the last is moderately cohesive associated to low permeabilities and to a resistance of the soil that varies from 1 to 3 kg/m3. Lastly, the area presents conditions geologic-geothecnic for sanitary filler, but with measures for the impermeabilización of the base of sanitary filler, to control the filtration of having leached, to maintain stable the formed structures, and to adapt a system of drainage of evacuation of the waters of pluvial precipitation.